A societal provenance analysis of the First World War service records held at the National Archives of Australia. Issue 2 (3rd May 2020) - Condé, Anne-Marie
ABSTRACT: This article offers a societal provenance analysis of the First World War personal service records held at the National Archives of Australia as Commonwealth Records Series B2455. It describes the communities of people and communities of records with which the series has its origins. Since creation, the records have enabled intricate interactions between individuals, families, government agencies and communities. They have facilitated personal, local, and national processes of grieving and commemoration, and bridged spatial, temporal and emotional distances. They have contributed to national projects such as the Roll of Honour at the Australian War Memorial, and the provision of pensions and support for veterans and their families. Their use by historians continues to shape our understanding of the history of the war. Access to the records helps build new personal identities, and new online communities of users. It is suggested that all these interactions are part of the history of the records we now have. The losses in the records, the gaps and silences, are also identified.